The role of FAS gene variants in inflammatory bowel disease - Demir, Ayhan; Kahraman, Resul; Candan, Gonca; Ergen, Arzu (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Analysis of genes thought to be important in IBD have shown that more than half of IBD-related genes are also associated with other autoimmune diseases. The aim of this study was to detect a possible association between the polymorphisms of the (-670 A/G, -1377 G/A) FAS gene promoter and susceptibility to IBD in the Turkish population. Materials and Methods: 125 patients with IBD including 73 ulcerative colitis and 52 Crohn's disease and also 101 healthy controls without any pathological signs of IBD. Real-time PCR technique was used to detect FAS polymorphisms in this study. Results: Analysis of FAS -670 A/G polymorphism indicated that frequency of GG genotype was increased in patients compared to controls significantly (p<0.001). Also, AG genotype (p<0.001) and A allele (p<0.001) frequencies were higher in controls than patients. Analysis of FAS -1377 G/A polymorphism revealed that frequency of AA genotype was increased in patients compared to controls meaningfully (p<0.001). Additionally, GG genotype (p<0.001) and G allele (p<0.001) frequencies were increased in controls when compared to patients. Conclusion: FAS -670A/G GG genotype seemed to be as a protective allele against to IBD, however AA genotype and A allele were associated with elevated risk of IBD. In the FAS -1377G/A polymorphism, frequencies of the G allele and GG genotype were observed to be protective against IBD whereas AA, GA genotypes, and A allele frequency increased in the patient group.